Medicinal potentials of the faveleira (Cnidoscolus quercifolius) and its uses in human health: a brief review (Research, Society and Development, 2021)
The Caatinga, exclusively brazilian biome, harbors great biodiversity and medicinal potentials in some plant species beneficial to human health, such as Cnidoscolus quercifolius, a native plant of this biome, popularly known as favela or faveleira, which is widely used in folk medicine in the northeastern hinterland. of Brazil. In this perspective, the present study aimed to discuss the medicinal uses of the faveleira (C. quercifolius) in northeastern popular medicine. This is a descriptive cross-sectional study, such as a literature review, developed from analyzes in scientific works published between 2001 and 2020, made available in the Google Scholar database, using the descriptors: “faveleira medicinal”, “faveleira medicina popular” “Cnidoscolus quercifolius” e “Cnidoscolus quercifolius medicina popular”. From the data collected, it was observed that the faveleira (C. quercifolius) is widely used in Northeastern folk medicine in the treatment of inflammatory processes, pain, infections, scarring and others, besides having antitumor activities. Therefore, it is notorious as the faveleira (C. quercifolius), has wide medicinal properties, being used over several generations in treatments for the recovery of human health.